AGILE APPROACHES, FOR E-BUSINESS SOLUTIONS STRATEGY, AT THE GOVERNMENT LEVEL - Cristian Brancu; Oana Turcu; Marius Stefan; Madalina Popp (Journal of Research and Innovation for Sustainable Society)
Modernity is characterized by major transformations and evolutions, which have penetrated into the depths of all levels of human existence, in all economic, political and social spheres, thus significantly increasing the quality of life. The Information Society is the model of society in which the main good is information itself. Although the accelerated development of information and communication technologies (ICT) is the process behind the evolution of the information society, the new model of society means much more than technological progress. In the technological age, action plans and policies are being developed to meet the challenges, the most important technology being ICT, which allows information to be processed and conveyed in a revolutionary way. The information society is the ICT-based knowledge society. Information society technologies will evolve in the direction of being at the fingertips of the knowledge process, by generating, storing, and transmitting knowledge. Knowledge is the result of the information management process, thus promoting innovation, economic development, and decision-making in an efficient and transparent way. Knowledge and scientific information are of enormous importance in the global information society, by: supporting innovation, promoting economic development, making decisions in an efficient and transparent way, at the governmental level and especially for the implementation and use of intelligent technologies in the development of the degree of digitization of public services through financing provided by European funds and the National Recovery and Resilience Plan. In order to move on to building the knowledge society, it is necessary to reduce the digital gap, which accentuates disparities in development, excluding groups and even countries, from the benefit of information and knowledge. The limiting factor in development will be related to the human capacity to assimilate and develop these technologies, to use them in new fields of activity, for new products and services